The Attention Window: A Narrative Review of Limitations and Opportunities Influencing the Focus of Attention. Issue 2 (3rd April 2017) - Hüttermann, Stefanie; Memmert, Daniel
ABSTRACT: Purpose : Visual attention is essential in many areas ranging from everyday life situations to the workplace. Different circumstances such as driving in traffic or participating in sports require immediate adaptation to constantly changing situations and frequently the conscious perception of 2 objects or scenes at the same time.Method : The attention window task, a measure of attentional breadth, in which people must attend to 2 equally attention-demanding stimuli simultaneously, was introduced. This article provides a narrative review of studies using this task and outlines different factors that might influence the attention window .Results : Differences in the spatial distribution of attention result, for example, from effects of age or physical activities as well as from emotional processes and those affected by current motivation, while gender does not have any influence. The window is represented as an ellipse with greater attentional breadth along the horizontal axis than the vertical axis, and it is about 5 to 6 times smaller than the human visual field.Conclusion : Not only everyday occurrences but also situations in sport games—for example, having an overview of the opponent, teammates, and the ball—require the ability to pay visual attention to 2 peripheral objects and continuously changing situations. Therefore, the application or avoidance of different strategies and factors is discussed to improve and adjust behavior in those situations.